2022
DOI: 10.1242/dev.198853
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and activity-dependent signaling in the developing cerebral cortex

Abstract: Calcium influx can be stimulated by various intra- and extracellular signals to set coordinated gene expression programs into motion. As such, the precise regulation of intracellular calcium represents a nexus between environmental cues and intrinsic genetic programs. Mounting genetic evidence points to a role for the deregulation of intracellular calcium signaling in neuropsychiatric disorders of developmental origin. These findings have prompted renewed enthusiasm for understanding the roles of calcium durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 317 publications
(465 reference statements)
0
12
0
Order By: Relevance
“…As calcium is well known to be an important regulator of many enzyme systems and biochemical pathways, the blood levels are tightly regulated and much of the liberated calcium is likely removed from the body by the kidneys and then ends up in the urine. Calcium signaling is important in the heart and vascular systems [ 19 , 20 , 21 , 22 ], in the brain [ 23 , 24 , 25 ], and in other tissues [ 26 , 27 ]. Some individuals who are at risk for kidney stones or gout could suffer from the consequences of high levels of calcium, and some biological systems may also be affected if the removal is not sufficient once the increases in calcium liberation become chronic and a secondary disease risk develops that was not evident on Earth.…”
Section: Responses Of Humans To Space Flight and Living In Leomentioning
confidence: 99%
“…As calcium is well known to be an important regulator of many enzyme systems and biochemical pathways, the blood levels are tightly regulated and much of the liberated calcium is likely removed from the body by the kidneys and then ends up in the urine. Calcium signaling is important in the heart and vascular systems [ 19 , 20 , 21 , 22 ], in the brain [ 23 , 24 , 25 ], and in other tissues [ 26 , 27 ]. Some individuals who are at risk for kidney stones or gout could suffer from the consequences of high levels of calcium, and some biological systems may also be affected if the removal is not sufficient once the increases in calcium liberation become chronic and a secondary disease risk develops that was not evident on Earth.…”
Section: Responses Of Humans To Space Flight and Living In Leomentioning
confidence: 99%
“…22 Calcium (Ca 2+ ) is an important secondary messenger molecule and regulates the activity of many signaling molecules and proteins. 23,24 The concentration of Ca 2+ ions significantly increases in AD and plays an important role in the pathology of this disease. 25 It has also been found that an increased Ca2+ level is involved in the hyperphosphorylation of tau in AD.…”
Section: Admentioning
confidence: 99%
“…Although calcium release from the Endoplasmic Reticulum (ER) and store-operated calcium entry (SOCE) are common mechanisms in all cell types, neurons have additional contributions through Voltage-Gated Calcium Channels (VGCCs) and calcium-permeable ionotropic glutamate receptors such as NMDA receptors (NMDARs). Thus, in neurons, NMDARs, VGCCs, SOCE, and ER-mediated calcium release are the major routes contributing to local and global calcium elevations and activation of intracellular signaling pathways ( 2 , 3 , 4 , 5 ). Many processes in neurons, such as gene expression, transcription, and alternative splicing, are shown to be regulated in a calcium-dependent and calcium channel–specific manner ( 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%